Managers’ Compensation in a Mixed Ownership Industry: Evidence from Nursing Homes - Huang, Sean Shenghsiu; Hirth, Richard A.; Smith, Dean G. (Frontiers in Public Health, 2016)
An extensive literature is devoted to differences between for-profit and nonprofit health care providers’ prices, utilization and quality. Less is known about for-profit and nonprofit managers’ compensation and its relationship with financial and quality performance. The aim of this study is to examine whether for-profit and nonprofit nursing homes place differential weights on financial and quality performance in determining managers’ compensation. Using a unique eight-year dataset on Ohio nursing homes, fixed-effect regression models of managers’ compensation include financial and quality performance as well as other explanatory variables concerning firm and market characteristics and manager qualifications. Among for-profit nursing homes, compensation of owner-managers and non-owner managers are compared. Compensation of for-profit managers are significantly positively associated with profit margin and return-on-assets, while compensation of nonprofit managers does not exhibit any consistent relationship with financial measures. Compensation of neither for-profit nor nonprofit managers is significantly related to quality measures. Nursing home size and managers’ years of experience are the only consistent determinants of compensation. Owner-managers earn significantly higher compensation than non-owner managers and their compensation is less related to nursing home performance. Finding that home size and experience are strong determinants of compensation, and the association with ownership and financial performance for for-profit nursing homes are as expected. The insignificant relationship between compensation and quality performance is potentially troublesome